Rent Seeking and Democracy in Latin America: What Drives What? - César Calderón; Alberto Chong (Inter-American Development Bank, Research Department, 2006)
Drawing on previously unused objective institutional data, we provide evidence for the causal link between rent-seeking behavior and democracy in Uruguay, a country where both rent-seeking behavior and political shifts have varied widely in the last 80 years, but where ethnolinguistic heterogeneity and income inequality have remained historically low. The latter helps better identify some pure political interactions and how they are linked with rent-seeking outcomes. We find that the presence and duration of democratic regimes appear to have been conducive to a decrease in rent-seeking actions in Uruguay, although the reduction in rent seeking does not appear to have had a bearing on the quality of democratic regime in the country. While the duration of democratic regime may impact rent-seeking behavior, rent seeking also displays a causal link to democratic duration.
Keywords: 330; Rent-Seeking; Demokratie; Kausalanalyse; Uruguay